The imperial cult in the Latin west : studies in the ruler cult of the western provinces of the Roman Empire - Fishwick, Duncan, 1929- (Religions in the Graeco-Roman World, 2004)
This volume focuses on the headquarters of provincial cults and the principal features of the worship offered there on behalf of the province. Evidence for provincial centres survives in various forms of varying degress of reliability but, while no standard pattern emerges, it seems clear that every province established a permanent base that served similar cultic, administrative, recreational and ideological purposes. Traces of provincial worship are more fleeting but a rough picture can be reconstructed of priestly regalia and of the calendar, rites and associated liturgy and ceremonial that marked the differing cults of individual provinces. Both studies conclude with an overview of the main conclusions and are profusely illustrated with over a hundred plates or diagrams.